Self-efficacy and students' readiness for providing nursing care through telenursing - Karra, Aulya Kartini Dg; Juwita, Helmi; Qasim, Muhammad; Yusuf, Saldi (Science Midwifery, 2025)
The advancement of technology has transformed the way nursing care is delivered. This study aimed to assess self-efficacy and readiness among nursing students in providing nursing care through telenursing at STIKES Amanah Makassar. Research design was a mixed-methods with a sequential explanatory consisting of two phases. The first phase used a retrospective quantitative approach with a standardized questionnaire. The second phase employed a qualitative approach through in-depth interviews. The results indicated that all students had high self-efficacy (100%), but their readiness to implement telenursing varied, where students’ high readiness (88.2%) and moderate (11.8%). Qualitative analysis revealed that although students were confident in their basic nursing skills, they still faced challenges with the technical aspects and adaptation to telenursing technology. Self-efficacy and readiness played a significant role in students' ability to provide nursing care through telenursing. All students have high self-efficacy were better prepared to face mental and technical challenges, including technology adaptation. While most students showed good readiness, there was still a need for strengthening technical skills and understanding of telenursing. Although each student showed a high level of self-efficacy, there were differences in their preparedness to use telenursing.